The Role of Islamic Religious Education Supervisors in A Successful Curriculum 2013 - Khalifaturrahmah Khalifaturrahmah (CV. ADIBA AISHA AMIRA, 2021)
The purpose of this article is to discuss the important role of Islamic Religious Education supervisors in the successful implementation of the 2013 curriculum. The important roles of Islamic Religious Education supervisors in the successful implementation of the 2013 curriculum include: 1) managing change management, Islamic Religious Education supervisors as managers and leaders of Islamic Education must be able to lead and influence the citizens of Islamic Religious Education to implement changes in Islamic Religious Education from KTSP to Islamic Religious Education with the 2013 curriculum; 2) being able to develop a culture of Islamic Religious Education, Islamic Religious Education as an agent of cultural change needs to formulate plans, development strategies, and monitor and evaluate the development of Islamic Religious Education culture; 3) carrying out academic supervision, helping teachers develop their abilities in managing the learning process to achieve learning objectives; 4) implementing learning management, Islamic Religious Education supervisors are able to lead effective learning that communicates high expectations for their students